1883 Wis. Sess. Laws 315, ch. 151, tit. 5, § 38. - (:unkn) unknown (General Publisher, 1883)
The powers conferred upon the said council to provide for the abatement or removal of nuisances, shall not bar or hinder suits, prosecutions or proceedings in the courts according of law. Depots, houses or buildings of any kind, wherein more than twenty-five pounds of gun powder are deposited, stored or kept at any one time . . . within the limits of said city are hereby declared and shall be deemed public or common nuisances.
--
Keywords: GUN POWDER STORAGE